Boosting methanol production via plasma catalytic CO2 hydrogenation over a MnOx/ZrO2 catalyst. Issue 8 (22nd March 2023) - Zhang, Xuming; Sun, Zhi; Shan, Yun; Pan, Hua; Jin, Yuzhen; Zhu, Zuchao; Zhang, Liancheng; Li, Kai
Abstract : Boosted methanol production over MnO x /ZrO2 catalyst could be achieved via plasma-assisted catalytic CO2 hydrogenation at ambient temperature and pressure. Abstract : Hydrogenation of carbon dioxide (CO2 ) to methanol is considered as a potential approach to simultaneously mitigate global warming and energy crisis issues. As an effective and economic oxide, MnO x is widely used as a promoter in catalytic CO2 hydrogenation, but it is rarely directly used as a catalyst in this reaction due to its poor activity. Herein, boosted methanol production over a MnO x /ZrO2 catalyst was carried out via plasma-assisted catalytic CO2 hydrogenation at ambient temperature and pressure. A space–time-yield value of methanol of 4.5 mgMeOH gcat −1 h −1 and a synergy factor of 87 were achieved with a stable performance over five cycles and 36 h. The in situ diffuse reflectance infrared Fourier transform spectroscopy and gas-phase FTIR spectra results indicate that the key intermediates over the MnO x /ZrO2 catalyst shifted from (bi)carbonates species to HCOO and CH3 O species in the plasma-assisted process. The methanol formation route was thus established. The beneficial effect of the plasma was the generation of excited species (such as, CO2 +, and H), which could be effectively hydrogenated to HCOO and then further to CH3 O by the favorable catalytic effect of MnO x . This study proposed a new strategy for catalyst design and methanol synthesis at ambient temperature and pressure.